Juvenile angiofibroma: etiology, diagnosis, treatment - Marzęda, Madalena; Blicharz, Agnieszka; Drozd, Małgorzata; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Juvenile angiofibroma is a rare neoplasm of the nasopharynx. It occurs almost exclusively in boys during adolescence. It is a richly vascularized neoplasm which, despite its benign histopathological character, tends to invasive growth and recurrence. The aim of the study is to review current data on juvenile angiofibroma. Brief description of the state of knowledge: Juvenile angiofibroma primary develops on the posterolateral wall of the nasal cavity, growing out of the wedge-palatal opening. Common symptoms resulting from its location, there are bleeding and nasal obstruction. Tumor diagnosis is based in imaging tests - CT and MRI, in which juvenile angiofibroma exhibits some distinctive features. CT and MR examinations demonstrate the typical the location and route of spread of juvenile angiofibroma and allow to assess the extent of the tumor. The angiography allows for confirmation diagnosis of a vascular tumor and enables preoperative embolization. Surgical treatment is the most common therapeutic procedure and irradiating the tumor, depending on its location. Due to the vascularnature of the tumor, the basic preoperative procedure is tumor vessel embolization, which allows reducing blood loss during surgery. Conclusions: Juvenile angiofibroma shows some characteristic features - it occurs at a similar age, in one sex and in one localization in the organism. Due to the invasive tumor growth, the risk of bone destruction and relapse, the role of imaging tests is important, allowing the diagnosis of a tumor at an early stage of its development.